Managing Online Auctions: Current Business and Research Issues - Pinker, Edieal J.; Seidmann, Abraham; Vakrat, Yaniv (Management Science, 2003)
The Internet's computational power and flexibility have made auctions a widespread and integral part of both consumer and business markets. Though online auctions are a multi-billion dollar annual activity, with a growing variety of sophisticated trading mechanisms, scientific research on them is at an early stage. This paper analyzes the current state of management science research on online auctions. It develops a broad research agenda for issues such as the behavior of online auction participants, the optimal design of online auctions, the integration of auctions into the ongoing operation of firms, and the use of the data generated by online auctions to inform future trading mechanisms. These research areas will draw from applied and theoretical work spanning management science, economics, and information systems.